Successful study : skills for teaching assistants and early years practitioners - Ritchie, Christine; Thomas, Paul (New York : Routledge, 2014)
'Successful Study is a guide for students embarking upon an education related Foundation Degree without previous study experience. It is aimed at those re-entering Higher Education (HE) after a long gap or for those who left school without thinking about going to university to study and are now starting HE study for the first time. The world of study at university can be a daunting and bewildering place for new students unfamiliar with the academic processes such as writing essays and presenting portfolios. This book offers clear and straight-forward explanations of how to prepare for study, how to work at higher education level and how to tackle assignments. This new edition has been fully updated to include:Clear links to work-based practices throughoutAdvice for students with disabilityGuidance on using e-resourcesTips for managing your learning and increasing motivation How to think criticallyReflective practiceWith case studies, tasks and opportunities for reflection, this accessible book has been specifically designed for those on Teaching Assistant, Early Years or related Foundation Degrees and will be an essential resource for those wanting to find the answers to study questions quickly and easily'--
'Successful Study is an essential guide for students embarking upon an education related Foundation Degree without previous study experience. The world of study at university can be a daunting and bewildering place for new students unfamiliar with the academic processes such as writing essays and presenting portfolios. This book offers clear and straight-forward explanations of how to prepare for study, how to work at higher education level and how to tackle assignments. Covering all aspects of educational study, and based on the experiences of real education professionals, this new edition has been fully updated to include: - Clear links to work-based practices throughout - Advice for students with disability - Guidance on using e-resources - Tips for managing your learning and increasing motivation - How to think critically - Reflective practice With case studies, tasks and opportunities for reflection, this accessible book has been specifically designed for those on Teaching Assistant, Early Years or related Foundation Degrees and will be an essential resource for those wanting to find the answers to study questions quickly and easily'--
Keywords: Study skills -- Handbooks, manuals, etc; Teachers' assistants -- Training of; Education, Preschool -- Handbooks, manuals, etc